2022
DOI: 10.1097/jfn.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Complex Suicide: A Case Series

Abstract: Suicide is a common manner of death typically carried out via a specific mechanism. When a suicidal act is committed using more than one method, it is called a complex suicide. A complex suicide can be divided into planned and unplanned. We present three cases of complex suicide in which multiple methods were used and a previous history of self-harm was present. This case series highlights the significance of a detailed medicolegal death investigation, including interviews with relatives and other witnesses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Suicide represents a victim’s decision to end their life. However, complex suicide involves the simultaneous use of two or more methods [ 1 ]. A planned complex suicide is rare [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Suicide represents a victim’s decision to end their life. However, complex suicide involves the simultaneous use of two or more methods [ 1 ]. A planned complex suicide is rare [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In India, an analysis of data over five years revealed that the most common methods of suicide were hanging (51.5%) and poisoning (26.7%) according to the National Crime Records Bureau (NCRB, 2018). Men were the predominant victims, with the highest incidence among those aged 18-30 years (34.9%), followed by those aged 31-45 years (31.6%) [ 1 ]. There are two types of suicide: simple and complex.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations